2016
DOI: 10.1038/srep31209
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated immune system networks in war veterans with PTSD is an outcome of altered miRNA expression and DNA methylation

Abstract: Post-traumatic stress disorder patients experience chronic systemic inflammation. However, the molecular pathways involved and mechanisms regulating the expression of genes involved in inflammatory pathways in PTSD are reported inadequately. Through RNA sequencing and miRNA microarray, we identified 326 genes and 190 miRNAs that were significantly different in their expression levels in the PBMCs of PTSD patients. Expression pairing of the differentially expressed genes and miRNAs indicated an inverse relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 63 publications
(83 reference statements)
2
53
0
1
Order By: Relevance
“…AC011899.9, C20orf199, LINC00599, MIR548A3, RP11-290F5.2, and SNHG5). Numerous studies in the blood of subjects with PTSD report differences in microRNA (miRNA) and noncoding RNAs (ncRNA) [46][47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…AC011899.9, C20orf199, LINC00599, MIR548A3, RP11-290F5.2, and SNHG5). Numerous studies in the blood of subjects with PTSD report differences in microRNA (miRNA) and noncoding RNAs (ncRNA) [46][47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these genetic results converge with evidence from epidemiologic cohort studies documenting the role of stressrelated disorders such as PTSD in autoimmune diseases, 49 case-control studies showing elevations of immune-related biomarkers in women with PTSD, 50,51 and epigenetic studies pointing to the role of the immune system in PTSD etiology. [52][53][54] Of note, it has been previously suggested that PTSD may be "a systemic disorder rather than one confined to the mind". 55 Further work is needed to determine whether PTSD has genetic overlap with immune disorders broadly and the causal direction between disorders.…”
Section: Discussionmentioning
confidence: 99%
“…To understand specific pathogenic pathways linking diverse etiologic factors to colorectal cancer, it is critical to fully consider potential etiologic heterogeneity. Furthermore, the MPE methodology is readily applicable to research of any human neoplastic [5, 47] and nonneoplastic [4851] diseases possessing substantial disease heterogeneity [3]. …”
Section: Framework Of Mpe Researchmentioning
confidence: 99%